Lichens "travelling" in smokers' cars are suitable biomonitors of indoor air quality. (August 2019) - Paoli, Luca; Maccelli, Caterina; Guarnieri, Massimo; Vannini, Andrea; Loppi, Stefano
Graphical abstract: Highlights: Car cabins of smokers may be contaminated by nicotine and heavy metals. Lichens ( Evernia prunastri ) travelled for 2 months in smokers' and non-smokers' cars. After travelling in smokers' cars, they accumulated nicotine and heavy metals. Lichens in smokers' cars showed a 60% reduction of their vitality. Abstract: In this work, two hypotheses have been tested: 1) that lichen transplants "travelling" in smokers' cars accumulate relevant amounts of nicotine and heavy metals from cigarette smoke, and 2) that such exposure affects their vitality. Lichen samples ( Evernia prunastri ) were exposed for two months inside the cabin of 10 volunteer's cars, equally distributed between smokers and non-smokers. Travelling in a smoker's car for two months increased the content of nicotine and heavy metals (Al, As, Cd, Cr, Cu, Ni, Pb and Sb) in the lichen. Exposed to Control (EC) ratios revealed an indoor uptake also for Cu and Sb in non-smoker's cars, caused by traffic pollution. A smoke factor, calculated as the ratio between values of smokers' and non-smokers' cars, indicated a 85.6-fold contribution for nicotine and contributions in the range 1.2 (Pb) to 2 (Ni) for heavy metals; in addition, after travelling in smokers' cars, lichens showed a remarkable (60%) reduction of their vitality, as indicated by the potential quantum yield of primary photochemistry. The study demonstrated that the effects of indoor pollution by cigarette smoke can be detected using lichen transplants.